Filtrasi Air dari Arang Ketapang sebagai Media Pengendalian Daya Rusak Air di SMP 6 Kota Dumai - Lady Asia; Zaldi Harfal; Dandi Rama Wijaya; Annisa Fitri; Indah Pujiati T.M; Evi Suryawati (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this research is to make socialization about the benefits of the ketapang fruit which has not been utilized by SMP 6 Dumai. Ketapang fruit that is burned into ketapang charcoal can actually be used for water purification and the results of the tested water filter are clear, odorless and tasteless. In research on simple miniature water filtration using ketapang charcoal, it turns out that the use of ketapang charcoal can change the pH of the water close to the pH of neutral water. Filter results with ketapang charcoal can change the pH to close to neutral pH and suitable for consumption, where the water suitable for consumption is at a pH of 6.5-8.5. In peat water obtained pH = 7.93; rust water obtained pH = 7.9; clay water obtained pH = 7.53; ditch water obtained pH = 6.3 and river water obtained pH = 7.9. From this research, it is convinced to the community that ketapang charcoal can be used to purify water and neutralize the pH of the water.